Cost-Effectiveness of Domestic PD-1 Inhibitor Camrelizumab Combined With Chemotherapy in the First-Line Treatment of Advanced Nonsquamous Non–Small-Cell Lung Cancer in China - Qiao, Liu; Zhou, Zhen; Zeng, Xiaohui; Tan, Chongqing (Frontiers in Pharmacology, 2021)
Objective Camrelizumab is the first domestic PD-1inhibitor approved to be combined with chemotherapy as a first-line therapy for advanced nonsquamous non-small-cell lung cancer (NSCLC) in China. This purpose of this study was to determine whether use camrelizumab in the first-line setting is cost-effective compared with traditional chemotherapy or imported PD-1inhibitor pembrolizumab in China. Material and Methods A Markov model was built to simulate 3-week patients transitions over a lifetime horizon from the perspective of Chinese healthcare system. Health states included stable disease, first progression, second progression and death. Direct comparison between first-line camrelizumab in combination with pemetrexed and carboplatin (CPC) and pemetrexed plus carboplatin (PC) was performed by calculating transition probabilities from the CameL trial. Indirect comparison between first-line CPC and pembrolizumab in combination with pemetrexed and platinum (PPP) was performed by calculating transition probabilities using network meta-analysis. Costs in the Chinese setting were collected from local public database and literatures. Sensitivity analyses explored the uncertainty around model parameters. Results In the primary analysis, first-line CPC gained an additional 0.41 quality adjusted life-year (QALY) with an incremental 3,486 costs compared with PC, which resulted in an incremental cost-effectiveness ratio (ICER) of 8,378 per QALY gained. In the secondary analysis, first-line PPP yielded an additional 0.10 QALYs at an incremental cost of 6,710, resulting an ICER of 65,563 per QALY gained. Conclusion From the perspective of Chinese healthcare system, our findings supported that first-line CPC was a cost-effective treatment strategy compared with traditional PC chemotherapy and the imported PD-1 inhibitor combined with platinum-based chemotherapy (PPP) for advanced nonsquamous NSCLC patients without targetable genetic aberrations. This analysis provided strong evidence for promoting the widespread use of first-line CPC in China, and to some extent stimulated the enthusiasm for the development of domestic cancer drugs.